Sayang Sayang Disayang Program / Nur Alya Natasha Mohd Nazeri and Noor Lina Mohd Hisam - Mohd Nazeri, Nur Alya Natasha; Mohd Hisam, Noor Lina (Universiti Teknologi MARA, Negeri Sembilan, 2023)
“Sayang Sayang Disayang” Program was organized by students in the 3rd semester of the Bachelor of Sports Science (Honours), Faculty of Sports & Recreation Science UITM Negeri Sembilan Branch, Seremban Campus in collaboration with Sekolah Menengah Kebangsaan Cheras Jaya on 29 November 2022 from 7 am until 1 pm. The program took place at SMK Cheras Jaya, Selangor with a total of nearly 80 disabled students. The purpose of this program is to make the community out there aware of the goal to be achieved, which is to share and reveal details of Recreation for Persons with Disabilities. Each participant was given exposure to understand Disabled People, especially when related to basic knowledge of camping-themed recreation such as how to set up a tent, how to use first aid, knotting and exploring. The exposure to these activities is not often and readily available.